Front Cover: Organocatalytic Desymmetrization of Meso‐Aziridines Via Asymmetric Intramolecular Rearrangement (Eur. J. Org. Chem. 33/2021). Issue 33 (26th August 2021) - Costanzo, Martina; Cortigiani, Mauro; Gillick‐Healy, Malachi W.; Kelly, Brian G.; Monasterolo, Claudio; Adamo, Mauro F. A.
Abstract : The Front Cover shows, in analogy with butterflies that undergo change of shape through their life cycle, the transformative rearrangement of bicyclic meso‐aziridines to form cyclopentenones. In this unprecedented reaction, chirality was liberated from an achiral precursor and was set free to fly to make drug precursors. More information can be found in the Full Paper by C. Monasterolo, M. F. A. Adamo et al.